The Construction and Performance of a Novel Intergroup Complementary Code - Wenzhun Huang; Shanwen Zhang (Universitas Ahmad Dahlan, 2013)
On the basis of the analyses for intergroup complementary (IGC) code and zero correlation zone complementary code, a novel IGC code has been proposed to adapt M-ary orthogonal code spreading spectrum system or quasi-synchronous CDMA system. The definition and construction methods of the new IGC codes are presented and an applied example is given in this paper. Theoretical research and simulation results show that the main advantages of the novel IGC code are as following: The code sets of the novel IGC code is more than IGC code under the same code length. The zero correlation zone length is longer than the intergroup IGC code, but shorter than the intergroup IGC code. Under the same code length, the auto-correlation performance of the novel IGC code is better than that of the IGC code, and both are of similar cross-correlation performance.